Employee Performance Based on Information Technology, Work Stress, and Work Life Balance as an Implementation of SDG’s No. 8 at PT PLN Indonesia Power UPB Asam-Asam. - Saleh, Muhammad; Hermawan, Sigit; Sriyono (Jurnal Manajemen, 2025)
Employee performance plays an important role in organizational success, especially in the energy sector which faces various challenges and changes. Employee performance also plays a crucial role in maintaining smooth operations and meeting national energy needs, especially at PT PLN Indonesia Power UPB Asam-Asam. This study aims to examine the effect of information technology, work stress, and work-life balance on employee performance at PT PLN Indonesia Power UPB Asam-Asam. With a quantitative approach, this study involved 125 respondents selected using the Slovin sampling method from a total population of 181 employees. Data were collected through questionnaires using a Likert scale and analyzed using multiple linear regression. This research is expected to provide strategic insights to improve employee performance, especially in facing the challenges of a dynamic energy industry.